Mandibular reconstruction with anterolateral thigh free flap and bridging plate: a retrospective study of 34 oncological cases - Ottaviano, Caterina; Goker, Funda; Cammalleri, Marcello; Fior, Andrea; Favero, Vittorio; Rizzo, Tommaso; Lobbia, Guido; Colapinto, Gianluca; Albanese, Massimo; Del Fabbro, Massimo; Barbera, Giorgio (Frontiers in Surgery, 2025)
IntroductionThe surgical gold standard following mandibular resection is reconstruction with a vascular osteocutaneous free flap. However, not all patients are suitable candidates for this type of procedure due to local or systemic contraindications or the critical anatomy of the remaining healthy bone. This study aimed to evaluate the outcomes of reconstruction with an anterolateral thigh (ALT) free flap in combination with a reconstruction plate as an alternative in such situations.MethodsThis retrospective case series included 34 oncological patients treated with ALT and reconstruction plate to restore mandibular bone defect following mandibulectomy. Seven patients who experienced serious postoperative complications received additional surgery involving the replacement of titanium plates [three with custom-made plates using computer-aided design (CAD)/computer-aided manufacturing (CAM) methods]. For evaluation, the following data were collected from the patients: gender, smoking habits, information about surgery (such as type of demolition, type of reconstruction plate used, and duration), the pathological node involvement, the application of radiotherapy (pre- or postoperative), the onset of complications (type of complication, time to complication, management strategy), and follow-up data. The follow-up period of the patients ranged from 3 months to 7 years. The follow-up assessments were based on both clinical and radiological methods, with CT scans performed at 1, 3, and 6 months.ResultsThirteen out of 34 patients developed early or late complications and were candidates for reoperation. Six of them died before undergoing additional surgery. The complications that were observed included flap failure, complications related to the plate (exposure, fracture, dislocation), development of sarco-radionecrosis, and recurrence. Seven subjects received additional surgery, including the removal and replacement of the reconstruction plates (custom-made plates in three patients).ConclusionThe surgical protocol described in this paper represents a promising option mostly suitable for geriatric patients who show relatively poor health status and advanced tumor stages.